Inositol Metabolism in Plants: VII. Distribution and Utilization of Label from Myoinositol-U-(14)C and -2-(3)H by Detached Flowers and Pistils of Lilium longiflorum - Kroh, M. (1970)
When detached flowers or isolated pistils of Lilium longiflorum are given myoinositol-U-(14)C or -2-(3)H as dilute solution through the severed pedicel, label is quickly distributed by the vascular system. In the case of pistils, a pattern of labeling in ovary, style, and stigma is obtained which indicates that products of myoinositol metabolism are utilized in the biosynthesis of exudate (secretion product) of the stigma and style as well as for components of pistil cell walls. Pollination had no discernible effect on labeling pattern.